Academic help‐seeking interactions in the classroom: A microlongitudinal study. (7th September 2022) - Davison, Kyle; Malmberg, Lars‐Erik; Sylva, Kathy
Abstract: Background: Help‐seeking research has traditionally inferred behavioural responses to the need for help from post‐hoc reflections and experiments outside of the classroom context. Aim: We aimed to gain an ecologically valid understanding of the help‐seeking process by examining the association between pupils' task‐specific perceptions and their help‐seeking interactions with teachers and peers during lessons. Sample: Participants were 290 pupils in Years 4–6 (aged 8.22–11.48) and 12 teachers in 12 classrooms in three schools across two local authorities in South East England, UK. Method: The microlongitudinal data consisted of 6, 592 task‐specific reports. Pupils reported on their task understanding and need for help and their help‐seeking (teacher and peer) and help‐giving behaviours at the end of each lesson. On average, pupils completed 25.44 reports across 14.64 lessons, 13 school subjects and 4.80 days. Teachers reported on pupils' academic performance. Data were analysed using two‐level logistic and multinomial logistic regressions. Results and conclusions: Task‐specific understanding and need for help were associated with help‐seeking and help‐giving behaviour during lessons. Understanding was associated also with the type of help sought and given among classmates and appeared to influence whether pupils were help‐seekers or help‐givers during peer interactions. There was an apparent reciprocity in peer help‐seeking interactions, occurring namely among girls and higher performers. Overall, girls were more likely than boys to seek and give help across tasks. Pupils for whom English was an additional language were less likely than classmates to seek help when they needed it. The study (1) sheds new light on the dynamics of everyday help‐seeking interactions in the classroom, (2) provides a conceptual framework for researchers interested in reciprocal processes of social interaction in self‐regulated learning, and (3) highlights groups who might benefit from intervention.